Enhanced mechanical properties of polyimide composite fibers containing amino functionalized carbon nanotubes. (27th October 2016) - Dong, Jie; Fang, Yuting; Gan, Feng; An, Jinyin; Zhao, Xin; Zhang, Qinghua
Abstract: Carbon nanotubes (CNTs) have been gained attention and interest to be as ideal reinforcement fillers due to their exceptional theoretical mechanical properties for a long time. To date, the reinforcing effect of the CNTs in most composite systems is still not satisfied. In the present study, by incorporating a novel NH2 -MWCNTs/NMP suspension into the polyimide matrix in situ polymerization, a series of PI/NH2 -MWCNTs composite fibers have been fabricated using wet-spinning technique. Detailed studies based on different spectroscopic characterizations suggested that there exist multiple interfacial interactions between NH2 -MWCNTs and polyimides (PIs) including the hydrogen bonding and π-π interaction. Wide-angle X-ray scattering measurements revealed the evolution of the aggregation structure of these composite fibers during heat-drawing process, and the results illustrated that the incorporated amino functionalized CNTs showed beneficial effects on the packing and orientation of PI molecular chains. Attributed to the above advantages, the resulting composite fiber containing 0.4 wt% NH2 -MWCNTs presented a tensile strength of 2.41 GPa (approximately a 47% increase over neat PI fiber), and the modulus of 99 GPa (27% raises compared with neat PI fiber). Meanwhile, dimensional stability of the PI fibers also has been improved by this effective approach.